Remote hemorrhage from the site of craniotomy Hemorragia à distância da área da craniotomia - José Alberto Landeiro; Marlo Steiner Flores; Mário Alberto Lapenta; Alexandre C. Galdino; Bruno C.R. Lázaro (Arquivos de Neuro-Psiquiatria)
Postoperative intracranial hemorrhage is a serious and sometimes a fatal neurosurgical complication. Hemorrhage occurring at regions remote from the site of intracranial operations comprises an uncommon affection, most ignored by the assistant physicians. It bares a still incomprehensive pathophysiology, despite several theories trying to explain it. Looks like a common sense that the presence of the remote site hemorrhage cannot be related to concomitant presence of hypertension, coagulopathy or undiscovered lesions. We report three cases of postoperative hemorrhages occurring in a remote site of supratentorial craniotomies, two patients presented cavernous sinus meningeoma and one patient was submitted to intracranial vascular surgery. Hemorragia intracraniana de ocorrência em pós-operatório é grave complicação das cirurgias intracranianas. O aparecimento de foco hemorrágico em regiões distantes ao sítio operatório original é considerado incomum, e muitas vezes ignorado pelos médicos assistentes. A fisiopatologia envolvida no processo não é de todo compreendida, apesar das diversas teorias já propostas. São apresentados três casos de hemorragia á distancia da área cirúrgica, no pós-operatório de dois pacientes portadores de meningeoma do seio cavernoso e de um submetido à clipagem de aneurisma intracraniano.